Decentralisation and fiscal performance in Central and Eastern Europe - Makreshanska mladenovska, Suzana; Petrevski, Goran (Taylor & Francis Ltd, 2021)
This paper provides empirical evidence on the association between decentralisation and budget deficits of the general government for a panel of 11 former transition countries during 1991–2018, controlling for the effects of various demographic, institutional, and macroeconomic variables. We provide evidence that decentralising government activities in Central and Eastern Europe (CEE) has favourable effects on the fiscal position of general government. Also, we show that the greater reliance on intergovernmental grants as a source of finance of local governments does not have detrimental effects on the overall fiscal discipline. Therefore, we cannot support the so-called ‘common pool’ hypothesis, which predicts that intergovernmental transfers lead to higher public expenditure, thus exacerbating the fiscal imbalances of the general government. On the other hand, we show that the effects of revenue decentralisation depend critically on the specific measure of local government revenue.
Keywords: Fiscal decentralisation; budget deficits; Central and Eastern Europe; panel data models